2019
DOI: 10.1021/acs.jchemed.9b00354
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Green Chemistry in the Curriculum: Building Student Skills in Systems Thinking, Safety, and Sustainability

Abstract: Chemistry educators have a responsibility to teach students about the essential role the field of chemistry has in a sustainable future for the planet. Chemical products, such as pharmaceuticals, plastics, electronics, agrochemicals, and building materials, all benefit society yet unintended consequences resulting from the production and use of these products compel chemists to develop new technologies which minimize their harm. The Committee on Professional Training (CPT)’s recently adopted Supplement on “Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 80 publications
1
97
0
1
Order By: Relevance
“…In a further 30 reviewed papers, the integration of green chemistry into the curriculum was mentioned, some also in the context of the main benefit of improving chemical safety. In addition, 31 papers addressed a strong synergy between chemical safety and green chemistry goals [27,[78][79][80]. Some papers (n = 27) focus on integrating green chemistry metrics into traditional chemistry teaching [81], while others also compare traditional ex-perimental work to experimental work optimized with green chemistry principles [82][83][84].…”
Section: What Are the Main Purposes Of The Reviewed Papers?mentioning
confidence: 99%
See 3 more Smart Citations
“…In a further 30 reviewed papers, the integration of green chemistry into the curriculum was mentioned, some also in the context of the main benefit of improving chemical safety. In addition, 31 papers addressed a strong synergy between chemical safety and green chemistry goals [27,[78][79][80]. Some papers (n = 27) focus on integrating green chemistry metrics into traditional chemistry teaching [81], while others also compare traditional ex-perimental work to experimental work optimized with green chemistry principles [82][83][84].…”
Section: What Are the Main Purposes Of The Reviewed Papers?mentioning
confidence: 99%
“…The results of the literature review suggest that updating chemistry teaching and learning with laboratory experimental work optimized from green chemistry perspectives simultaneously provides a safer approach to chemistry and ensures a safer environment by minimizing exposure to potentially hazardous chemicals and reducing the generated waste. Aubrecht et al [27] pointed out the importance of teaching chemical safety by recognizing a significant overlap between reflection on the 12 green chemistry principles and the RAMP paradigm (recognize hazards, assess the risks of hazards, minimize the risks of hazards, and prepare for emergencies) [80].…”
Section: Key Findings and Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Supplementing core topics with sustainability has been achieved through the efforts of initiatives such as Green Chemistry Education. 68 While sustainable concepts and green chemistry have been primarily showcased in upper level elective 69,70 and organic chemistry lab courses, 71,72,73,74 efforts have been made to expand the curriculum into introductory 75,76,77 and general chemistry courses. 78,79,80 The lack of green chemistry content in organic chemistry textbooks has been explored and it has been suggested that connections to societal issues and sustainability contribute to the development of leadership skills.…”
Section: Key Takeawaysmentioning
confidence: 99%